229k views
5 votes
Which of the following expressions is equivalent to 3?

7 + (-4)
-7 + 4
7 - (-4)
-7 - (-4)

User John Erck
by
5.5k points

2 Answers

0 votes

Answer:

A

Explanation:

wiedjwurfffffffffjjjjjjjjjjjjjj

User Rawburner
by
5.1k points
5 votes

Answer:

answer is 7 + (-4)

Explanation:

7 + (-4) = 3

-7 + 4 = -3

7 - (-4) = 11

-7 - (-4) = -3

hope i helped

User Leaniman
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.